STRATEGI AKTIVE LEARNING DALAM PEMBELAJARAN BAHASA ARAB DI STAIN PONOROGO 2014 - Kasnun, Kasnun (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: Learning is an activity that is not limited to the school context only. It can be done anywhere and anytime as the availability of space and time. The system of Mastery learning deals with how students master the material at least 80%. Mastering the material needs extra effort from teachers as well as students. The use of Mastery learning through STAD method in Arabic learning can enhance cooperation between the personal in groups, provide insight, deepen understanding, and train students to express ideas into question so that the atmosphere of group discussion is more optimal. Furthermore, the application of STAD method in Arabic learning provides the valuesÂ  and sense of responsibility for individual or group.Â ÙØ§Ù ØªÙÙ ÙØ£ ÙØ§ÙÙÂ  Ù ÙØ£ ÙÙ Ø³ÙØ±Ø¯ØªÙØ§ ÙÙÙÙ ÙØ£ ÙÙÙÙ Ø§ÙÙØ¥Ù ØØ¨Ø³ØÙ Ø©ÙØ³Ø±Ø¯ÙÙØ§ Ø©Ø¦ÙØ¨ÙØ§ ÙÙ Ø±ØµØÙÙ ÙØ§ ÙÙÙØ¹ØªÙØ§ ÙØ§ÙÂ ÙÙØ¹ ÙÙØ±Ø·ÙØ³Ù Ø¨ÙØ§Ø·ÙØ§ ÙØ¹Ø¬ )Mastery learning( Ø·ÙÙ ÙÙØ¹ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ§Ø¸Ù ÙØ§ÙÙ .ÙØ§ÙÙÙØ§Ù ØªÙÙÙØ§ Ø©ÙÙØ§ÙÙØ¥ Ø¨Ø³ØÂ ÙÙØ³Ø±Ø¯ÙÙØ§ ÙØ¨Ù ÙÙ Ø©Ù Ø¯Ø§ÙØ¬Ø§ Ø©ÙÙØ§ÙÙØØ§ ÙÙØ¥ Ù Ù Ø¬ÙØªÙØ§ Ø§Ø°Ù Ø¬Ø§ØªØØ§ .)Ø©Ø¦Ø§ÙÙØ§ ÙÙ ÙÙÙØ§Ø«Ù ( 80 % ÙÙÙØ£Ø§ ÙÙØ¹ Ø©ÙØ³Ø§Ø±Ø¯ÙØ§ Ø¯Ø§ÙÙÙØ§Â ÙÙÙÙ Ø©ÙØ¨Ø±Ø¹ÙØ§ Ø©ØºÙÙØ§ ÙÙÙØ¹Øª ÙÙ STAD Ø©ÙÙØ±Ø·ÙØ§Ø¨ )Mastery learning(Ø¨ÙÙØ³ÙØ£Ø§ ÙØ§Ø¯Ø®ØªØ³Ø§Ù .Ø¨ÙØ§Ø·ÙØ§Ù ÙÙØ³ÙÙØ£Â ÙÙØ´ ÙÙ Ø¡Ø§Ø±ÙØ¢Ø§Ù Ø±Ø§ÙÙÙØ£Ø§ ØØ±Ø· ÙÙØ¹ Ø¨ÙØ±Ø¯ØªÙØ§Ù ÙÙÙÙØ§ Ø¡Ø§Ø·Ø¹Ø¥Ù Ø©Ø¹Ø§ÙÙØ¬Ø§ ÙÙ Ø¯Ø§Ø±ÙÙØ£Ø§ ÙÙØ¨ ÙØ¹Ø§ÙÙØ¬Ø§ ÙÙØ¹ÙØ§ ÙÙ ÙØ±Ù ÙØ£Â ÙÙÙÙØ§ Ø³Ø±ØºÙ Ø©ÙØ¨Ø±Ø¹ÙØ§ Ø©ØºÙÙØ§ ÙÙÙØ¹Øª ÙÙ STAD ÙÙØ¨Ø·Øª ÙØ§Ù Ø§Ø°ÙÙÙ .Ø§Ù ÙØ Ø©Ø¹Ø§ÙÙØ¬Ø§ ÙÙ Ø´Ø§ÙÙÙØ§ ÙÙÙÙ ÙØªØ Ø©ÙØ¦Ø³ÙØ£Ø§Â .ÙÙÙØ±Øº ÙØ¹Ù ÙÙØ³ÙÙØ£ ÙØ¹ Ø¨ÙØ§Ø·ÙØ§ ÙØ¯Ù Ø©ÙÙÙØ¤Ø³ÙÙØ§ ÙÙØ¹ÙÙ